2002
DOI: 10.1046/j.1440-1673.2002.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose distribution and morbidity after high dose rate brachytherapy for prostate cancer: Influence of V150 and V200 parameters

Abstract: The purpose of this study is to identify factors predicting morbidity in patients undergoing high dose rate (HDR) brachytherapy boost with external beam irradiation for prostate cancer. Acute and late morbidity data were collected for 104 prostate cancer patients treated with an HDR boost together with external beam radiotherapy. Significant urinary and rectal morbidity were correlated with urethral and rectal point doses, and the proportions of the target volume receiving 100%, 150% and 200% (V200) or more of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In a series of 64 patients treated with two HDR-BT fractions of 9 Gy and 50.4 Gy EBRT, Pinkawa et al (27) reported an association between a urethral D 1 in either of the implants and the urinary morbidity scores. Duchesne et al (28) found that acute and late urinary morbidity was associated with the prostate V 200 but were unable to find an association between the urethral dose and toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…In a series of 64 patients treated with two HDR-BT fractions of 9 Gy and 50.4 Gy EBRT, Pinkawa et al (27) reported an association between a urethral D 1 in either of the implants and the urinary morbidity scores. Duchesne et al (28) found that acute and late urinary morbidity was associated with the prostate V 200 but were unable to find an association between the urethral dose and toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…No clinical evidence has been reported of the importance of homogeneity of dwell times, but large dwell times could lead to hot spots of volumes receiving a high dose around these specific dwell positions (32,39). These volumes are generally avoided if possible (32,40). This is supported by the American Brachytherapy Society and the Radiation Therapy Oncology Group 0321 study, stating that a minimum number of 14 catheters is required to avoid unnecessary hot spots (34,41).…”
Section: Discussionmentioning
confidence: 99%
“…Duchesne et al (25) reported that target volume receiving 200% of the prescribed dose correlated significantly with acute and late toxicity. Pinkawa et al (18) reported urethral maximum dose in a single HDR fraction $15 Gy as a risk factor, with significant influence on urinary toxicity at 1.5 and 3 years after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve better treatment results in the future, we should take into account dose-volume histograms (DVHs) of the target and organs at risk. Although numerous reports have described HDR brachytherapy combined with conventional EBRT for localized prostate cancer (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), few studies have investigated the DVH and toxicity of HDR brachytherapy combined with hypofractionated EBRT for this cancer.…”
Section: Introductionmentioning
confidence: 99%